Three new synonyms among Australian Thripinae (Insecta: Thysanoptera) - Mound, Laurence A. (Zootaxa, 2012)
The North American entomologist, A.A. Girault, arrived in Australia in late 1911 at the age of 28, to take up an appointment as economic entomologist to the Queensland Bureau of Sugar Experimental Stations near Cairns. He published extensively on the taxonomy of Australian parasitic Hymenoptera, but achieved particular notoriety through issuing a series of 63 privately published papers before his death in 1941. Gordh et al. (1979), in reproducing facsimile editions of each of these papers, provided an extensive overview of Girault’s life and opinions, many of which were expressed outrageously on a wide range of topics. In these papers Girault made available over 900 new species-group names, mostly Hymenoptera but with 139 that applied to Australian Thysanoptera. Unfortunately, the identity of these species has been a continuing problem. The publications include no biological information. Most species were described in three or four lines from single, often damaged specimens, and distinguished from each other on colour rather than structure. The original slide preparations are available in the Queensland Museum, Brisbane, but these are remarkably poor, with cover glasses broken, labels inadequate and scarcely legible, and many bearing multiple species. As a result of extensive studies on the Australian thrips fauna over the past 50 years, 77 of the 139 Girault Thysanoptera names are now placed into synonymy, including two new synonyms discussed below. The purpose of this note is to establish the nomenclatural validity of these synonyms, according to the Code of Zoological Nomenclature, so that they can be included in an expanded web-based account of Australian Terebrantia (Mound et al. 2012).